The complete mitochondrial genome of the boky-boky, Mungotictis decemlineata, the first representative of the Malagasy carnivores (Mammalia, Carnivora, Eupleridae). (3rd March 2016) - Hassanin, Alexandre; Veron, Géraldine
Abstract: The complete mitochondrial genome of the boky-boky, Mungotictis decemlineata, was sequenced using overlapping PCRs. The genome is 16, 910 base pairs in length and contains the 37 genes found in a typical mammalian genome: 13 protein-coding genes, 22 transfer RNA genes and 2 ribosomal RNA genes. The overall base composition on the L-strand is A: 32.1%, C: 27.8%, G: 14.5%, T: 25.6%. The control region of M. decemlineata includes both RS2 and RS3 tandem repeats.